2014
DOI: 10.1037/a0034984
|View full text |Cite
|
Sign up to set email alerts
|

Does premarital education decrease or increase couples’ later help-seeking?

Abstract: Interventions intended to prevent relationship distress are expected to enhance relationship satisfaction and, in turn, reduce the need for later couples counseling. We test this prediction against an alternative possibility: participation in preventive interventions may operate as a gateway for later help-seeking, paradoxically increasing receipt of later couples counseling. A cross-sectional study of 2,126 married individuals examined whether participation in premarital education covaried inversely or direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…Given that couples learn to identify the aspects of their relationship that are most challenging over time (Williamson et al, 2014), it is promising that relationship education may serve to facilitate couples seeking help. However, it may be important to bear in mind that Williamson et al (2014Williamson et al ( , 2018 studied associations between a use of relationship education likely intended to be purely preventive (premarital intervention) and not the provision of relationship education to established, married couples (as was the case for the sample, here). In either case, little is yet known about couples who received marriage education and subsequently sought marital therapy, and whether or not having done so is associated with gains from marital therapy.…”
mentioning
confidence: 99%
“…Given that couples learn to identify the aspects of their relationship that are most challenging over time (Williamson et al, 2014), it is promising that relationship education may serve to facilitate couples seeking help. However, it may be important to bear in mind that Williamson et al (2014Williamson et al ( , 2018 studied associations between a use of relationship education likely intended to be purely preventive (premarital intervention) and not the provision of relationship education to established, married couples (as was the case for the sample, here). In either case, little is yet known about couples who received marriage education and subsequently sought marital therapy, and whether or not having done so is associated with gains from marital therapy.…”
mentioning
confidence: 99%
“…First, disseminating universally offered couple education for couples at early stages of the relationship (e.g., in relation to marriage or transition to parenthood) may function to increase later helpseeking. In a recent study by Williamson et al (2014), findings showed that couples who received premarital education were three times more likely to seek couples therapy later in their marriage, than couples who did not attend, suggesting that premarital education operates to lower barriers for later help-seeking. Second, disseminating brief formats for indicated prevention may enhance help-seeking.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent study by Williamson et al. (), findings showed that couples who received premarital education were three times more likely to seek couples therapy later in their marriage, than couples who did not attend, suggesting that premarital education operates to lower barriers for later help‐seeking. Second, disseminating brief formats for indicated prevention may enhance help‐seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Premarital education attendance in the United States has risen from 9.7% of couples who were married in the 1940s to 52.2% of those married in the 1990s . Couples who attend premarital education are more likely to attend relationship counseling, especially when they are at-risk (Williamson, Trail, Bradbury, & Karney, 2014). Although premarital education has increased, Doss, Rhoades, Stanley, Markman, and Johnson (2009) reported that individuals in their second marriages were much less likely to attend premarital education for subsequent relationships than for first marriages.…”
Section: Couple Therapymentioning
confidence: 97%